Strategic Planning Procedure: An Imperative for Effective Management of Higher Education in Nigeria - Modebelu, M.N.; Joseph, Anebi (Mediterranean Journal of Social Sciences, 2012)
Research reports and observations have indicated the absence of quality planning in the management ofhigher education in Africa. This appears to be one of the major constraints to the effective management ofhigher education in majority of the institutions all over Africa. The paper examined â€œstrategic planningprocedure as an imperative for effective management of higher education in Nigeriaâ€. Two hundredrespondents (i.e. 100 lecturers, and 100 administrative officers) from five Federal Universities from southeast geo-political zone of Nigeria were sampled and used for the study. Four research questions guided thestudy. Four point Likert-type rating scale with 21 â€“ item researchersâ€™ self-made questionnaire was used fordata collection. Mean computation was used to analyzed the research questions. Pearson Product Momentwas used to establish the reliability of the instrument. Findings include: low level achievement of highereducation goals, identification of seven-item elements of effective management, identification 8-itemcomponents of strategic planning procedure and its low level application in higher institutions in Nigeria.